Pengaruh Kualitas Pelayanan, Kemudahan Aplikasi, Dan Jumlah Armada Terhadap Keputusan Konsumen (Studi Pada Mahasiswa Universitas Islam Malang) - Muhammad Nur Muzakki; Muhammad Mansur; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This Study Aims To Determine The Effect Of Service Quality, The Effect Of Ease Of Application, And The Effect Of Fleet Numbers Partially And Simultaneously On Consumer Decisions In Choosing Online Motorcycle Taxi Services (Studies On Grabbike Consumers At Islamic University Of Malang. Population And Sample Are Grabbike Consumers At Islamic University Of Malang Data Analysis In This Study Uses SPSS Version 20. The Technique Of Sampling In This Study Uses Quantitative Methods, Quantitative Data Itself Is Data Measured In A Numerical Scale (Numbers), Which Can Be Divided Into Interval Data And Ratio Data. Regression Coefficient And Simultaneous Service Quality, Ease Of Application, And Number Of Fleets Have A Positive Effect On Consumer Decision. Keywords: The Influence Of Service Quality, The Effect Of Ease Of Application, The Influence Of The Number Of Fleets.